A Critique of the Book Decline and Fall of the Sasanian Empire: The Sasanian–Parthian Confederacy and the Arab Conquest of Iran - Afshin Khosrosani (پژوهش‌نامۀ انتقادی متون و برنامه‌های علوم انسانی)
Historians and scholars have cited many reasons for Sasanian’s defeat by the Arab. In 2008, Parvaneh Pourshariati revived this topic by publishing the book Decline and Fall of the Sasanian Empire: The Sasanian–Parthian Confederacy and the Arab Conquest of Iran. With an innovative and rare methodology, she presented a new and rare narrative of the fall of the Sasanian. Analyzing written sources and archaeological evidence, Pourshariati acknowledges that the Sasanian kingdom consisted of the Sasanian-Parthian confederacy and by not supporting the Sasanian on behalf of Parthian dynasties, the Arab succeeded to come to an end the Sasanian kingdom. Some of the shortcomings of the book are the acceptance of some narratives and interpretations uncritically, the lack of attention to the final impact of the Sasanian’s war with the Romans and its impact on the decline of this dynasty, the lack of proper analysis of archaeological evidence, and most importantly, little attention to environmental disasters and severe damage to the irrigation system of Mesopotamia at the end of the Sasanian epoch. The following article tries to examine these shortcomings and will evaluate the book in light of the mentioned cases.